Strengthening Mathematical Learning in Young School-Age Children Through a Didactic Module (Docentes 2.0 Journal, 2026)
Mathematical learning is fundamental to children's cognitive development; however, many children struggle to grasp key concepts, negatively impacting their academic performance and highlighting the need to strengthen this process from an early age. The purpose of this research was to develop and integrate a didactic learning module designed to enhance mathematical learning in children aged 6 to 10, addressing the limitations of traditional teaching methods. The study was framed within the pragmatic paradigm, employing the hypothetico-deductive method, a mixed-methods approach, and a concurrent nested design. It was predominantly quantitative, quasi-experimental, and longitudinal, with a short-term focus. Qualitative assessments (structured observation) were administered to 6-year-old children, integrated with quantitative assessments (pretest-posttest) in children aged 7 to 10, enabling a comprehensive data analysis. For statistical analysis, the chi-square test was used to determine if the proportion of children who achieved an improvement of 20 percent or more was statistically significant. The results showed that 50% of participants reached this level of improvement, allowing the null hypothesis to be rejected and confirming the module's positive impact. Despite the small sample size, the evidence supports the module's effectiveness as a teaching tool with potential applications across various educational settings.
Keywords: Mathematical learning; early education; didactic module; playful methodologies; cognitive development